Pogojenost zakonodajne politike z naravo prava - Igličar, Albin (Pravni letopis, 2023)
Legislative policy is conditioned first of all by general social values. Then, the determination of the aims and means of legislative policy is limited by the objective material, social, political and cultural circumstances of global society. The following are the determinants that are set for legislative policy by constitutional frameworks and strategic-political documents. A successful legislative policy must also take into account the immanent nature of law. Therefore, it must start from (1) an integral view of law, (2) it must take into account its social function and (3) integrate legal norms into a non-contradictory system. The stated assumptions lead to the normative integration and legitimacy of legal institutes.
Keywords: družbene vrednote; narava prava; pravni instituti; zakonodajna politika